Advocating teaching and learning cycle derived from genre-based approach in teaching writing - Riswanto Riswanto (JRTI (Jurnal Riset Tindakan Indonesia), 2021)
When writing in English, the students of SMA 15 Padang found two obstacles. The first issue was that the teacher's approach did not motivate students to write. This challenge increased the second issue, namely the students' apathy. The pupils were unmotivated and uninterested in writing. In other words, the students were uninterested. To address the two concerns, the researcher did a classroom action research that involved five stages: developing the context, modeling and deconstructing the text, cooperative production of the text, autonomous construction of the text, and linking to relevant text. The study found that implementing a teaching and learning cycle built from a genre-based approach might improve the teaching and learning process in writing classes. This was evident from the results of a checklist observation, which revealed that virtually all pupils appreciated the manner the instructor taught and that the majority of them were engaged in their study. The questionnaire results also revealed that 96 percent of the students were interested in the teacher's method and 98.8 percent of the pupils were already engaged in learning. By recording 10 pupils in each cycle, those data were also validated to the results of the interviews. According to the interview data, the majority of the students expressed an interest in the teacher's method and writing in English. Finally, implementing a teaching and learning cycle developed from a genre-based approach might increase students' enthusiasm to write in English. Hopefully, it will be a significant contribution for the teacher and other scholars to teach and conduct research, particularly in the teaching of writing.